Learning Trajectory Flat Building Material Using Batik Besemah Context for Elementary School Students - Susanti, Novi; Zulkardi, Zulkardi; Indra Putri, Ratu Ilma; Susanti, Ely; Nusantara, Duano Sapta (Universitas Ma'arif Lampung, 2024)
Students experience difficulties in understanding the properties of flat shapes because learning is monotonous, so there is a need for innovation in learning flat shape material. This research aims to produce a learning trajectory for flat building materials using the context of besemah batik for elementary school students. This research uses a design research method which consists of three research steps, namely preparing for the experiment, the design experiment, and retrospective analysis. Data collection was carried out by providing student activity sheets and interviews. Data is analyzed by reducing data, presenting data, and making conclusions. The results of the research show that learning the trajectory of flat shapes using the context of besemah batik consists of four activities, namely 1) observe the besemah batik pattern, 2) redraw the besemah batik pattern, 3) writing down the characteristics of flat shapes. based on the pattern image on besemah batik, and 4) write definitions of various flat shapes and represent various flat shapes in the drawing. Based on the research, it can be concluded that the resulting learning trajectory can help students understand flat shape material.